Anticancer properties of 1,2,4-triazole derivatives (literature review) - I. V. Bushuieva; M. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Cancer is still one of the leading causes of death worldwide. Statistical data show that more than 130,000 people in Ukraine receive this diagnosis as a sentence every year. Cancer can affect any organ and eventually the whole body. In most cases, cancer is a tumor affecting epithelial, mucous, muscle, fat, and bone tissues. Also, processes related to malignant formations can occur in the blood and lymph. The main mechanism that triggers the process of formation of neoplasms is a violation of growth and, accordingly, cell division. They begin to grow uncontrollably, multiply, and can also migrate, spreading to nearby tissue structures, and later degenerate into atypical (malignant) ones. Cancer is one of the most life-threatening diseases. Literature data show that more than 90 % of cancer patients die due to chronic metastases. Cancer therapy involves the use of drugs that block the growth and spread of cancer cells by affecting certain molecular structures involved in the growth, progression, and spread of cancer. The diversity of the use of means for cancer therapy, namely, hormone therapy, the use of angiogenesis inhibitors and apoptosis inducers, has provided scientists with various options for finding effective means to fight this disease.